Pertarungan Harga Diri Carok pada Puisi-Puisi Karya D. Zawawi Imron: Studi Etnografi - Albaburrahim Albaburrahim; Ahmad Yasid; Sugerman Sugerman (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This research analyzes the self-esteem struggle of carok in poems by D. Zawawi Imron with an ethnographic approach. The poems by D. Zawawi Imron become the focal point to understand the complexity of Madurese culture, especially in the context of carok as a cultural phenomenon inherent in the identity of Madurese society. This type of research includes qualitative research with an ethnographic approach. The ethnographic approach is used because this research focuses on an in-depth understanding of the self-esteem context of Madurese carok culture as reflected in the poems by D. Zawawi Imron. Zawawi Imron, such as “Madura, Akulah Darahmu”, “Celurit Emas”, and “Pedang”. The results showed that the poems by D. Zawawi Imron is not only a literary work that stands alone, but also interpreted as a result of interpretation of real life about the carok self-esteem battle in Madurese culture. The poems by D. Zawawi Imron portrays Madurese people who view self-esteem as a form of courage, honor, and Madurese tradition.